Reservoir engineering handbook - Ahmed, Tarek H., 1946- (Gulf Professional Pub., 2001)
This book covers reservoir fluid behavior and properties, including laboratory analysis and reservoir fluid flow. It provides a guide to predicting oil reservoir performance through analysis of oil recovery mechanisms and performance calculations. It also explains the fundamentals of reservoir engineering and their practical application through a comprehensive field study. New material makes this volume a very comprehensive reference for the reservoir engineer or reservoir engineering student. -- Provided by publisher.
Keywords: Oil reservoir engineering.; Oil fields.; Gas reservoirs.; elektronické knihy; electronic books